The strategic partnership between Georgia and the United States: Vision wanted - Franziska Smolnik (Stiftung Wissenschaft und Politik (SWP), 2020)
Georgia's political leadership has been pursuing close ties to the United States and a geopolitical positioning in 'the West' at least since the presidency of Mikheil Saakashvili. A formal Strategic Partnership has structured the relationship since 2009. Donald Trump's "America First" policy and the transition to a supposedly less pro-American political leadership in Georgia have raised questions over the status of the bilateral relationship. Georgian-US ties remain close and have intensified in recent years. They are still essential to Tbilisi. But the two sides do not always associate the same expectations, functions and priorities with the Strategic Partnership. Washington prioritises democracy and rule of law, and corresponding reforms in Georgia. Tbilisi concentrates on security and defence and increasingly also economic and trade cooperation. The biggest obstacle to a further deepening of the relationship, however, is Washington's lack of a strategic vision for Georgia and the region. This strategic void places limits on Tbilisi's efforts to establish its own imagined geography in Washington. Without a clear US strategy the Strategic Partnership perpetuates Georgia's liminality, its suspension between "east" and "west". In this respect it resembles Georgia's Association Agreement with the European Union.
Keywords: 320